Preoccupied attachment style and beliefs about medicines in patients with Major Depressive Disorder - G. Santarelli; G. Sanfilippo; F. Benvenuti; L. Santoro; A. Nistri; A. Ballerini; V. Ricca (European Psychiatry, 2022)
Introduction Attachment style is defined by the American Psychological Association as “the characteristic way people relate to others in the context of intimate relationships”. Four attachment styles have been described: secure, fearful, preoccupied, and dismissing. While the effect of attachment style on psychotherapy was widely investigated, few studies have investigated its role in determining beliefs about medicines in patients with Major Depressive Disorder (MDD).